XL International Art Colony - Center for Contemporary Plastic Art. - Babic-Janeska, Gordana; Baseski, Ilija; Sekulic, Liljana (Skopje : SCCA (Soros Center for Contemporary Arts), 1997)
Antovska, Olgica ; Balac, Tanja ; Gelevska-Veljanova, Zaneta ; Gockov, Stojce ; Ivanov, Nikola ; Janaslieva, Slavica ; Markovska, Marija ; Masgnug, Kristin ; Milunovic, Mihael ; Kasiopea, Naumoska ; Pantev, Evgenij ; Popovski, Alexandar ; Popovski, Igor ; Popovski, Saso ; Raunik, Maja ; Salatoski, Ljupco ; Spinkoska, Emilija ; Tanevska, Tanja ; Filev, Dimitar ; Arnaudov, Simeon ; Bolea, Ayrelian ; Grabuloski-Bonach, Bogdan ; Milunovic, Mihael ; Pasima, Dimitru ; Saas, Bruno ; Srbinoski, Borce ; Vidzen, Ana ; Pavleski, Stanko ; Desoska, Monica ; Neskovic, Dusan
XL International Art Colony - Center for Contemporary Plastic Art, 1997
Engels & Macedonisch
boek